A Mineral Trioxide Aggregate Sealer Stimulated Mineralization - Gomes Filho, João Eduardo [UNESP]; Watanabe, Simone [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; de Moraes Costa, Mariana Teixeira [UNESP] (Elsevier B.V., 2009)
The aim of this study was to evaluate the rat subcutaneous tissue response to implanted polyethylene tubes filled with Endo-CPM-Sealer (Portland Cement Modified Sealer) (EGEO S.R.L., Buenos Aires, Argentina) compared with Sealapex (SybronEndo, Glendora, CA) and Angelus MTA (Angelus, Londrina, Brazil). These materials were placed in polyethylene and dentin tubes and implanted into dorsal connective tissue of Wistar rats for 7, 15, 30, 60, and 90 days. The specimens were prepared to be stained with hematoxylin and eosin or Von Kossa or not stained for polarized light. Qualitative and quantitative evaluations of the reaction were performed. Both materials caused mild to moderate reactions at 7 days that decreased with time. The response was similar to the control on the 30th day with Endo-CPM-Sealer and Angelus MTA and on the 60th day with Sealapex. Mineralization and granulations birefringent to the polarized light were observed with all materials. it was possible to conclude that Endo-CPM-Sealer was biocompatible and stimulated mineralization. (J Endod 2009;35:256-260)
Keywords: Biocompatibility; connective tissue; mineral trioxide aggregate